PENGARUH PENGGUNAAN GEL EKSTRAK DAUN PEGAGAN (Centella Asiatica L.Urb) TERHADAP KEJADIAN STRETCH MARK PADA IBU MASA NIFAS DI WILAYAH KERJA PUSKESMAS BONTOMARANNU: PENGARUH PENGGUNAAN GEL EKSTRAK DAUN PEGAGAN (Centella Asiatica L.Urb) TERHADAP KEJADIAN STRETCH MARK PADA IBU MASA NIFAS DI WILAYAH KERJA PUSKESMAS BONTOMARANNU - Nugrawati, Nelly; Ekawati, Nur; Wijaya, Ayu; Adam, Andi Muhammad (WELL BEING, 2025)
ABSTRACTBackground:Striae, also known as stretch marks or striae distensae, are skin changes that occur during pregnancy, appearing as light or reddish-dark lines, commonly found on the breasts, abdomen, buttocks, thighs, and calves. One of the treatments that can be used to reduce stretch marks is pegagan leaf gel (Centella asiatica). Objective:To determine the effect of pegagan leaf gel on stretch marks in postpartum mothers in the working area of Bontomarannu Health Center. Method:This study used a quasi-experimental design with a One-Group Pretest-Posttest Design approach, involving two groups: an intervention group and a control group. The population consisted of postpartum mothers in the working area of the Bontomarannu Health Center, East Kutai Regency. A total of 12 participants were selected using the total sampling technique. The research instruments included an observation sheet, and the intervention involved the application of pegagan leaf gel. Data were analyzed using the Wilcoxon test. Results:The results showed a significant difference in the experimental group with a p-value = 0.000. Conclusion:There is a significant effect of pegagan leaf gel application in both the intervention and control groups.